Sterilization of money inflows: difficult (Calvo) or easy (Reisen)? - Frankel, Jeffrey (Estudios de Economía, 2016)
Some countries undergoing exchange-rate-based stabilization and financial liberalization in Latin America and elsewhere have faced large capital inflows since 1991. Many have tried to sterilize the reserve inflows. Calvo and coauthors argue essentially that sterilization is more difficult than generally realized, due to the interest costs on sterilization bonds. Reisen argues essentially that sterilization in easier than generally believed. This paper reviews the issues in the simplest textbook model. The conclusions are that local interest rates are not likely to rise if the source of the disturbance is an exogenous capital inflow, but will rise if the disturbance is an increase is money demand or an increase in exports. In every case, sterilized intervention will leave interest rates higher than they would be if the inflow took place unsterilized. The case where the domestic money supply and the rest of the economy are insulated from foreign disturbances despite perfect capital mobility and a fixed exchange rate, which Reisen attributes to Southeast Asia, is seen to be the case where domestic agents are unresponsive to interest rates.